The effect of warm-up on postural sway in the dominant and non-dominant leg - Aliye Büyükergün; Abdullah Arguz; Ömer Çalışkan; Yağmur Kocaoğlu (Turkish Journal of Kinesiology, 2023)
Although the chronic effects of a long-term warm-up program have been widely studied, to our knowledge, the number of studies examining the acute effects of a single warm-up session on inter-limb balance asymmetries in symmetrical sports such as cycling is limited. The aim of this study was to examine the effect of warm-up on postural sway in the dominant and non-dominant leg in male bicycle athletes. Sixteen healthy young male volunteers who engage in cycling sports participated in the study. The participants' age was determined as 15.50±1.15 years, body weight as 56.06±7.79 kg, height as 169.87±4.98 cm, and sports experience as 4.31±1.25 years. The postural control performance on the dominant and non-dominant leg of the athletes was evaluated on Biodex Balance System balance device platform for 20 seconds before and after a 10-minute warm-up exercise performed at a constant pedaling frequency of 80 RPM on a bicycle ergometer. In the comparison of the pre-test to post-test dominant leg Overall Sway Index (t=3.456; p=0.004), Anterior-Posterior (Z=-3.160; p=0.002) and Medial-Lateral (Z=-2.428; p=0.015) postural control scores of the participants, a significant decrease was found in the post-test. It was determined that warm-up exercise can only improve acute postural control in the dominant leg. The effects of the study can be extended to different sports branches with symmetrical features in order to obtain comparable results.